Understanding Texts with the Help of Experimentation: The Example of Cupellation in Arabic Scientific Literature. (2nd April 2016) - Moureau, Sébastien; Thomas, Nicolas
Abstract : The article aims to show how experimentation can help us understand historical texts, by focusing on the specific case of cupellation in Arabic scientific literature. It also provides new information about cupellation in the Arab-Muslim Middle Ages. The article consists of translations of three of the most detailed accounts of cupellation: Hamdānī's Kitāb al-jawharatayn al-'atīqatayn (first half of the fourth/tenth century), Maslama b. Qāsim al-Qurṭubī, Rutbat al-ḥakīm (339–342/950–953), and Manṣūr b. Ba'ra, Kitāb kashf al-asrār al-'ilmiyya bi-dār al-ḍarb al-miṣriyya (615–635/1218–1238). These are accompanied by commentaries based on a series of experiments carried out in the course of archaeological research on cupellation, which are here used to shed new light on the medieval texts and resolve several problems in interpreting them.